2020
DOI: 10.1177/1524838020939119
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment, Youth Violence, Intimate Partner Violence, and Elder Mistreatment: A Review and Theoretical Analysis of Research on Violence Across the Life Course

Abstract: This article reports the results of a scoping review of the literature on life-course patterns of violence that span the developmental periods of childhood, adolescence, and early and middle adulthood. We also assess the evidence on elder mistreatment and its relation to earlier forms of violence. Additionally, we draw on theories and empirical studies to help explain the transmission of violence over time and relational contexts and the factors that appear to mitigate risks and promote resilience in individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 123 publications
(135 reference statements)
0
37
0
1
Order By: Relevance
“…Studies of IPV over one's life course have focused mainly on patterns of violence, revealing how early experiences of violence are associated with negative health outcomes and the perpetration and victimisation of violence during adolescence and adulthood, as well as across generations [25,26]. Life course analyses also examined the temporal sequence of IPV and other aspects of health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of IPV over one's life course have focused mainly on patterns of violence, revealing how early experiences of violence are associated with negative health outcomes and the perpetration and victimisation of violence during adolescence and adulthood, as well as across generations [25,26]. Life course analyses also examined the temporal sequence of IPV and other aspects of health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…A common process underlies all three treatment systems: strategies to protect oneself and one’s family from danger, leading to diverse mental health, child protection and criminal outcomes. Not only were most maltreating parents and criminals maltreated as children (Bowlby, 1944; Spinetta and Rigler, 1972; Weeks and Widom, 1998), but their children are at risk for all three conditions (Herrenkohl et al, 2020; Lippard and Nemeroff, 2020). All three conditions reflect danger to life itself (Ertl et al, 2019) and, when they occur in childhood, to accurate and complete information about danger in the future.…”
Section: Part 2: a 21st Century Plan For Improving Treatment And Treatment Systemsmentioning
confidence: 99%
“… Teaster and Brossoie (2016) proposed that the misuse of alcohol and other drugs can signal desperate attempts on the part of an adult child to cope with the stress and demands of caregiving, and to cover over feelings of inadequacy and unhealthy dependency on older adults. It is also important to note that substance abuse and depression are also consequences of child abuse and neglect ( T. I. Herrenkohl et al, 2013 , 2020 ), which indicates that they may play a pivotal, yet unstudied, role in the continuation and spread of abuse within families and across generations. Interestingly, a study by Kong and Moorman (2015) found that adult children who provided care to their once abusive and neglectful parents had more frequent symptoms of depression than those who had not been maltreated.…”
Section: Lifecourse Perspectivementioning
confidence: 99%
“…The tendency for abuse within families to spread across relationships is documented in numerous cross-sectional and a few longitudinal studies ( T. I. Herrenkohl et al, 2020 ). In fact, evidence suggests that adults who were abused as children are at significantly higher risk than are others for abusing and being victimized by an intimate partner, and, possibly, for mistreating their own children ( T. I. Herrenkohl et al, 2020 ). For some individuals, exposure to abuse is endured over many years ( T. I. Herrenkohl et al, 2020 ; Wilkins et al, 2014 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation